Macroprudential measures and housing markets: a note on the empirical literature - Essi Eerola (Bank of Finland, 2016)
The global financial crisis has led to increased attention on the relationship of household indebtedness and systemic risks. As a result, macroprudential measures aimed at reducing the risks have been introduced in many countries. This note reviews the recent empirical literature on these measures focusing on the housing market. Thus far, the literature mostly consists of cross-country studies using aggregate data and looking at a large set of different measures. The studies typically report associations between the measures and outcome variables of interest (often credit growth and house price appreciation), but do not assess the causal effects of the different measures or the underlying mechanisms. Exploiting household level data together with policy reforms, should be a useful step forward in understanding the effects of the measures and uncovering the mechanisms through which they operate. Focusing on micro-data would also allow studying the distributional effects of the measures. Understanding the distributional effects is important in its own right, but also because the ultimate goals of the macroprudential policies are related not only to the aggregate level of credit but also to the distribution of leverage.
URN:NBN:fi:bof-201606211228
Keywords: E58; G28; 330